2018
DOI: 10.1021/acs.jpcb.7b10970
|View full text |Cite
|
Sign up to set email alerts
|

Force Field Benchmark of the TraPPE_UA for Polar Liquids: Density, Heat of Vaporization, Dielectric Constant, Surface Tension, Volumetric Expansion Coefficient, and Isothermal Compressibility

Abstract: The transferable potential for a phase equilibria force field in its united-atom version, TraPPE_UA, is evaluated for 41 polar liquids that include alcohols, thiols, ethers, sulfides, aldehydes, ketones, and esters to determine its ability to reproduce experimental properties that were not included in the parametrization procedure. The intermolecular force field parameters for pure components were fit to reproduce experimental boiling temperature, vapor-liquid coexisting densities, and critical point (temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 60 publications
(119 reference statements)
1
18
0
1
Order By: Relevance
“…Another likely reason for the underestimation of the dielectric constant is the neglect of polarizability, which is common to most molecular models available to date. This hypothesis is supported by the fact that several transferable force fields also underestimate the dielectric constant [21][22][23].…”
Section: Pure Fluidsmentioning
confidence: 89%
See 1 more Smart Citation
“…Another likely reason for the underestimation of the dielectric constant is the neglect of polarizability, which is common to most molecular models available to date. This hypothesis is supported by the fact that several transferable force fields also underestimate the dielectric constant [21][22][23].…”
Section: Pure Fluidsmentioning
confidence: 89%
“…Caleman et al [21] presented an evaluation of the OPLS/AA and GAFF force fields and found that most of the models underestimate the dielectric constant. Núñez-Rojas et al [22] carried out a similar study on the TraPPE/UA force field and also found that the dielectric constant is typically underestimated, with an average deviation of about 37%. Zangi [23] investigated the OPLS/AA force field for alcohols, and found an average underestimation of the dielectric constant of about 33%.…”
Section: Introductionmentioning
confidence: 91%
“…To determine the performance of nonpolarizable force fields in reproducing properties apart from those used as the target in the parameterization procedure, Caleman et al in 2011 performed a benchmark to calculate eight properties for 146 organic liquids and found out that the dielectric constant was systematically below the experimental value for all the force fields . A similar benchmark was carried out for 41 polar liquids using the TraPPE-UA force field, and also, it was found that the dielectric constant was systematically below the experimental data . Recently, the solubility of alcohols, ethers, sulfides, ketones, esters, and thiols dissolved in water was determined for 12 molecules using the TraPPE-UA force field.…”
Section: Introductionmentioning
confidence: 92%
“…The CGenFF 66 produced the most accurate results for these properties. Efforts following those studies included refinement of alcohol compounds in the OPLS/AA force field, 73 using a fragment-based approach to improve liquid properties of saturated hydrocarbons, 74 parameterization of charges in OPLS/AA for 10 polar liquids, 75 tuning of the dielectric properties of chlorinated hydrocarbons, 76 a benchmark of 41 polar liquids using the TraPPe/UA force field, 77 validation of the SMIRNOFF force field 78 and, finally, a study of the interface tension of the water/oil interface. 79 The general conclusion from these studies is that liquid densities can be reproduced within 1%-2%, and energies have an accuracy of about 5-6 kJ/mol.…”
Section: Liquid Phasementioning
confidence: 99%
“…Dielectric constants (Equation 7) are significantly underestimated in most force fields. 34,55,77 Fluctuation properties such as β T (Equation 8) and α P (Equation 9) are challenging to reproduce since it takes a much longer simulations time to obtain converged values than, for example, the liquid density.…”
Section: Liquid Phasementioning
confidence: 99%